Florapal an ethnobotanical website of Flora Palaestina reflects changing patterns of plant use in this region during the mid-20th to 21st century - Sallon, Sarah; Myers, David; Jamous, Rana; Paavilineen, Helen; Fragman-Sapir, Ori; Abuzaitoun, Salam Yousef; Eisner, Deborah; Solowey, Elaine; Ali-Shtayeh, Mohammed S. (Ethnobotany Research and Applications, 2025)
Background: Flora Palaestina, a term first used by Linnaeus in the 18th century, describes plants native to the Holy Land, today comprising Israel, Palestinian Authority (West Bank), Gaza and Western Jordan. Consisting of ca. 2750 species and 114 families these plants have a long history of traditional use by Jews and Arabs; a rich legacy rapidly being lost as societies develop and modernise. Construction of Florapal an open-access website describing ethnobotanical uses of 316 Flora Palaestina species provides an important tool for preserving and researching this unique resource. Methods: Florapal contents are derived from combining previously unpublished surveys of plant use amongst Jewish and Arab populations in this region (1950-1979) with later surveys amongst the Arab population of West Bank and Gaza (1996-2016). Using separate but related information fields, Florapal preserves original descriptions of plant use, categorizes complaints/uses within defined body systems or states, and provides a potential interpretation of their mechanisms of action Results: Analysis of 2319 specific complaints/uses described in the Florapal website shows a higher prevalence of plant use in earlier surveys compared to later ones for various infections, infectious diseases, general non-specific symptoms, and culinary uses. Later surveys show increased plant use for endocrine/metabolic, cardiac, and infertility conditions and veterinary uses. These findings suggest the continuing popularity and adaptation of plant use to changing patterns of morbidity and social development during survey periods. Conclusions: Florapal an important educational resource preserves the historical legacy of plant use in this region, contributing to its conservation, research, and development Keywords: Ethnobotany, Flora Palaestina, Florapal website